PENGEMBANGAN MEDIA SCRAPBOOK PADA KETERAMPILAN MENULIS SISWA KELAS IV SD MUHAMMADIYAH KARANGBENDO - Oktafia Tri Hapsari; Yosi Wulandari (Universitas Ahmad Dahlan, 2019)
This study aims to determine the procedure for developing scrapbook media on the writing skills of fourth grade elementary school students of fiction story material, as well as knowing the feasibility of scrapbook media on the writing skills of fourth grade elementary school students. This research is included in the research (R&D) by using the ADDIE development model with the following stages 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subject of the trial was conducted by media experts, material experts, learning experts, students and teachers. Data collection is done by questionnaire, interview and documentation. Data analysis uses qualitative data analysis and quantitative data. The results of the study of the validation of 85% of media experts with excellent categories. the results of the validation of the material experts 89.6% with a very good category. The results of validation from learning experts 82.7% with very good category. The results of the teacher's response to the small group trial 95% with a very good category, student responses to the small group trial 94% with a very good category. The results of the teacher's response to the large group trial 95% with a very good category, student responses to the large group trial 96.8% with a very good category. The results showed that (1) the scrapbook learning media was produced in writing skills, (2) the results of the entire product trial were categorized very well with a score of 91.2. These results indicate that the scrapbook media is suitable for use in the learning process and supports students' writing skills.